2018
DOI: 10.3390/v10120666
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Highly Divergent Strain of Cell Fusing Agent Virus (CFAV) in Mosquitoes from the Brazilian Amazon Region

Abstract: Classical insect-specific flaviviruses (cISFs) have been widely detected in different countries in the last decades. Here, we characterize the near full-length genomes of two cISFs detected in mosquitoes collected in the city of Macapá, state of Amapá, Amazon region of Brazil. A total of 105 pools of female mosquitos were analyzed by next-generation sequencing (NGS). Comparative genomics and phylogenetic analysis identified three strains of cell fusing agent virus (CFAV) and two of Culex flavivirus (CxFV). All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…It has subsequently been detected in several Aedes and Culex spp. mosquitoes from locations in Asia, Africa and the American continent [40], and recently reported from Brasil [51]. AEFV is another ubiquituous ISF, previously also detected in mosquitoes from Italy and United States, following its initial characterization in Japan [5256].…”
Section: Discussionmentioning
confidence: 97%
“…It has subsequently been detected in several Aedes and Culex spp. mosquitoes from locations in Asia, Africa and the American continent [40], and recently reported from Brasil [51]. AEFV is another ubiquituous ISF, previously also detected in mosquitoes from Italy and United States, following its initial characterization in Japan [5256].…”
Section: Discussionmentioning
confidence: 97%
“…For example, the Amazon region is identified as the starting point for transmission of the yellow fever virus in a recent outbreak in Brazil that killed almost 700 people between December 2016 and March 2018 and the Amazon rainforest functions as a 'reservoir' region for several arboviruses [42]. Other studies have been identified novel virus presents in the mosquito microbiota in this region, in the host Aedes aegypti and anophelines [17,18,43], reinforcing the idea that our current knowledge about the diversity of viruses is still very limited. Furthermore, insect-specific virus (ISV) compose the majority of mosquito virome the virus-virus interactions may affect the transmission of some viral pathogens [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from our group have described unusual viral sequences from Flaviridae and Reoviridae families in Ae. aegypti mosquitoes in the Amazon [17,18]. Using an NGS metagenomic approach, this study aimed to identify novel viruses in Ae.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a rapid expansion of known members of ISFs and other insect-specific viruses, but little is known about their biology and maintenance in mosquito populations. This is true even for CFAV, an ISF first discovered in 1975 and with global distribution in a major vector species and sustained seasonal infection (Baidaliuk et al 2020; Jeffries et al 2020; Martin et al 2020; Ajamma et al 2018; Fernandes et al 2018; Bolling et al 2015; Yamanaka et al 2013; Espinoza-Gomez et al 2011; Cook et al 2006). The detection of infected larvae or pupae and lack of other known hosts has led to speculation that ISFs are vertically transmitted.…”
Section: Discussionmentioning
confidence: 99%